Interactive Learning Paper Model of Inguinal Canal - Tun, Ye; Myint, Yi Yi (2012)
The inguinal region is one of the most complex anatomic areas of human body even though it has been the subject of great interest to anatomists and surgeons because of its clinical importance. The aims of the study are to: 1. provide a simplification and in-depth understanding of the complex and confusing inguinal canal anatomy. 2. incorporate time-effective method in learning. 3. provide revision for coursework at any time and place. This study took place during the 2008–2009 academic year. The anatomical diagrams were prepared with the Microsoft word 2007 and printed on three A-4 papers. The inguinal canal was constructed using ordinary scissors and glue. The efficacy of the model construction is evaluated by testing 10 questions regarding the anatomy of inguinal canal before(pre-test) and after(post-test) doing the construction. The 5-point scale questionnaire was used to elicit the students’ views on different teaching methods in our university. The questionnaire with free comments section was completed by 62 second-year medical students (response rate 60.19%). Ninety six students performed the construction with most completing it within one hour. Scores on the anatomy pre-test and post-test were compared. The mean pre-test score was 8.406/10 and the mean post-test score was 9.309 /10. It was found that there was a significant increase in post-test score (P<0.05). The students also responded similarly to interactive sessions, practicals, tutorials and 3-D paper model (P>.05) in the 5-points scale questionnaire. We concluded that the 3-D paper model provides the opportunity to learn and correlate the spatial relations among the inguinal structures in a short period of time especially when taking constraints of time and the availability of other resources into account. Moreover, this model is inexpensive and easy to construct and a valuable supplement to conventional teaching methods.